An introduction to QED and QCD - Hautmann, F (Science and Technology Facilities Council, STFC, 2013)
These lectures present a heuristic introduction to gauge theories of electromagnetic and strong interactions, focusing on perturbative applications of the S matrix and the use of Feynman graphs in QED and QCD. They are complementary to the presentations of field theory in the Standard Model and Quantum Field Theory courses at this School. The approach followed in these lectures may be found in the textbooks given in Ref. [1]. Quantum field theory treatments may be found in the textbooks given in Ref. [2]. Secs. 1 and 2 discuss relativistic quantum mechanics and spin. Secs. 3 to 5 are devoted to interactions and scattering processes at tree level in QED. Sec. 6 extends the discussion to QCD. Secs. 7 and 8 consider loops and give an introductory discussion to renormalization.